Investigating the Body in the Victorian Asylum Doctors, Patients, and Practices - Wallis, Jennifer (Mental Health in Historical Perspective, 2017)
This book is open access under a CC BY 4.0 license. This book explores how the body was investigated in the late nineteenth-century asylum in Britain. As more and more Victorian asylum doctors looked to the bodily fabric to reveal the ‘truth’ of mental disease, a whole host of techniques and technologies were brought to bear upon the patient's body. These practices encompassed the clinical and the pathological, from testing the patient's reflexes to dissecting the brain. Investigating the Body in the Victorian Asylum takes a unique approach to the topic, conducting a chapter-by-chapter dissection of the body. It considers how asylum doctors viewed and investigated the skin, muscles, bones, brain, and bodily fluids. The book demonstrates the importance of the body in nineteenth-century psychiatry as well as how the asylum functioned as a site of research, and will be of value to historians of psychiatry, the body, and scientific practice.